2018
DOI: 10.1111/anu.12818
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of dietary xylooligosaccharide on growth and feeding performance, body composition and physiological responses of sobaity seabream ( Sparidentex hasta ) juvenile

Abstract: The aim of this study was to evaluate the effects of xylooligosaccharide (XOS) on growth performance, haemato‐immunological responses, body composition and digestive enzymes activity of sobaity seabream juvenile (Sparidentex hasta) with an average weight of 35.64 ± 0.30 g. Fish were fed with experimental diet containing 0, 5 and 10 g XOS kg−1 for 8 weeks. The obtained results indicated that dietary XOS did not change sobaity seabream growth, feed utilization and body composition (p > 0.05). The results of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…XOSs made from corn cobs using Aspergillus xylanase in Nile tilapia showed prebiotic effects (Van Doan et al, 2018. Morshedi et al (2018) used XOS from corn cobs and found no significant prebiotic effects compared to the control group. Azeredo et al (2017) discovered that XOS from corn cobs increased lysozyme activity but had no effects on total immunoglobulins, bactericidal activity, or complement content in experimental trials.…”
Section: Sources Of Xossmentioning
confidence: 99%
See 2 more Smart Citations
“…XOSs made from corn cobs using Aspergillus xylanase in Nile tilapia showed prebiotic effects (Van Doan et al, 2018. Morshedi et al (2018) used XOS from corn cobs and found no significant prebiotic effects compared to the control group. Azeredo et al (2017) discovered that XOS from corn cobs increased lysozyme activity but had no effects on total immunoglobulins, bactericidal activity, or complement content in experimental trials.…”
Section: Sources Of Xossmentioning
confidence: 99%
“…Moreover, XOSs fermentation by beneficial gut bacteria may benefit fish by providing energy from the simple soluble sugars produced and preventing the colonisation of pathogenic microbes in fish gut (Manning and Gibson, 2004;Vázquez et al, 2005). Systemic XOSs fermentation by Bifidobacterium species and LAB increases glycolysis and digestive enzyme activity (Guerreiro et al, 2016;Morshedi et al, 2018), resulting in improved growth performance and body composition of fish. However, adding XOSs to the diet of Sparidentex hasta did not affect intestinal lipase and amylase activities (Morshedi et al, 2018).…”
Section: Effects Of Dietary Xoss On Fish Growth Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Current researches of scholars in different directions are looking for ways to resolve such problems, which gets a great success in the use of green feed additive. Researches show some green feed additive, such as Chinese herbal medicines (Pu, Li, Du, Cui, & Xu, 2017;Wang et al, 2018), oligosaccharides (Lee et al, 2018;Morshedi et al, 2018) and probiotics (Lee et al, 2018;Wang, Li, & Lin, 2008) that can enhance the fish growth performance, immunity, product quality and improve the aquaculture environment. As a new green feed additive, exogenous feed enzymes are primarily produced by microbial fermentation, which is a natural, environmental-friendly and safe process (Ravindran & Son, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…FOS are not significantly digested in small intestine but fermented in the large intestine to selectively stimulate growth performance and survival of some health promoting bacteria such as lactobacilli and bifidobacteiral species (Wu et al, 2013). Supplementation of dietary prebiotics has been shown to improve the health and growth performance of various aquatic species (Safari et al, 2014;Eshaghzadeh et al, 2015;Guerreiro et al, 2015;Ali et al, 2016Ali et al, , 2017aAli et al, , b, c, 2018Morshedi et al, 2018). Therefore the current study was carried out to investigate the effect of dietary fructooligosaccharide supplementation on intestinal and liver histology, digestive enzyme activity, biochemical and immunological parameters of L. calcarifer fingerlings.…”
Section: Introductionmentioning
confidence: 99%